Criteria sets for primary Sjogren's syndrome are not adequate for those presenting with extraglandular organ involvements as their dominant clinical features - ALİBAZ ÖNER, FATMA (SPRINGER HEIDELBERG, 2017)
Patients with primary Sjogren's syndrome (pSS) may go undiagnosed or be misclassified due to the insidious nature and wide spectrum of the disease. The available several classification criteria emphasize glandular findings. We aimed to analyze the efficiency of various classification criteria sets in patients diagnosed on the clinical basis by expert opinion and to compare those pSS patients who fulfilled these criteria with those who did not. This is a multicenter study in which 834 patients from 22 university-based rheumatology clinics are included. Diagnosis of pSS was made on the clinical basis by the expert opinion. In this study, we only interviewed patients once and collected available data from the medical records. The European criteria, American-European Consensus Group (AECG) and American College of Rheumatology (ACR) Sjogren's criteria were applied. Majority of the patients were women (F/M was 20/1). The median duration from the first pSS-related symptom to diagnosis was significantly shorter in men (2.5 +/- 2.3 vs 4.3 +/- 5.9 years) (p = 0 < 0.016). When the European, AECG and ACR Sjogren's criteria were applied, 666 patients (79.9%) satisfied at least one of them. In total, 539 patients (64.4%) satisfied the European, 439 (52.6%) satisfied the AECG, and 359 (43%) satisfied the ACR criteria. Among the entire group, 250 patients (29.9%) satisfied all and 168 (20.1%) met none of the criteria. The rates of extraglandular organ involvements were not different between patients who met at least one of the criteria sets and those who met none. There is an urgent need for the modification of the pSS criteria sets to prevent exclusion of patients with extraglandular involvements as the dominant clinical features.
Keywords: Sjogren's syndrome; Classification criteria; Extraglandular involvement; Epidemiology; EUROPEAN CONSENSUS GROUP; RHEUMATOLOGY CLASSIFICATION CRITERIA; AMERICAN-COLLEGE; SYSTEMIC-DISEASE; DATA-DRIVEN; EPIDEMIOLOGY; PULMONARY; REGISTRY; COHORT